Malawi Standard Treatment Guidelines - Malawi Government: Ministry of Health (Malawi Government, 2021)
Medicine is a dynamic science and therefore it is important that publications such as the Malawi Standard Treatment Guidelines (MSTG) be revised at short intervals. Revision of the 3rd edition of the MSTG started with a consultative meeting of stakeholders followed by editorial meetings and finally the approval process by members of the National Medicines and Medical Supplies Committee. The MSTG includes key information on the selection, prescribing, dispensing and administration of medicines. It is designed as a digest for rapid reference and it may not always include all the information necessary for prescribing and dispensing. It should therefore be interpreted in the light of professional knowledge and supplemented as necessary by specialised publication and by reference to product literature. Pursuant to the African Union Assembly Abuja Declaration of 2005, Malawi like other member states of the Union aims at putting 15% of the National budget towards towards the health budget. Resources, particularly financial resources for health service delivery are often scarce. Prudent use of these resources through improved diagnosis, rational prescribing, dispensing and use of medicines is paramount. The MSTG aims at standardizing prescribing and dispensing practices. The 4th edition MSTG provides prescribers and dispensers with the currently recommended treatment as well as preventative schedules for most common disease states found in the country. I would like to thank all those who took time to review the previous edition. Your contributions are greatly appreciated. I look forward to your continued support and contributions to future reviews of the MSTG and other relevant publications.